Factors influencing hospital preparedness and resilience for emerging infectious diseases: a systematic review - Yuli Susanti; Seger Handoyo; Ernawaty Ernawaty; Wiwin Hendriani (AOSIS, 2023)
Hospitals have crucial roles during an outbreak of emerging infectious diseases. They are expected to manage the surge of patients while continuing essential health services. This study aims to investigate the factors that influence hospital disaster preparedness and resilience in facing emerging infectious disease threats. A systematic review was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) method. International electronic databases, including PubMed, Science Direct, ProQuest, and SAGE, were investigated for the research studies that were published between 2001 and 2022 in English-language. The inclusion and exclusion criteria were determined to extract factors or indicators influencing hospital disaster preparedness and resilience encounter emerging infectious diseases. For the initial 672 articles, we identified 16 articles that specifically addressed the aims of this review and formed the basis of the intended analysis. Seven factors influence hospital preparedness, with human resources and crisis management being the most important. The hospital's resilience has 18 factors that are classified according to the disaster phase. Hospital resilience is concerned with all phases of a disaster (mitigation, preparedness, response, and recovery), not just operational management during a disaster (as is preparedness).